2014
DOI: 10.4081/vsd.2014.5315
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian follicular dynamics in buffaloes during different estrus synchronization protocols

Abstract: The current study was carried out on 26 normal cycling buffaloes. Animals were divided into 4 groups according to the hormonal treatment regime. Group 1 included 11 buffaloes without hormonal treatment. Group 2: five buffaloes injected with one dose of 25 mg prostaglandin F2alpha (PGF2α) after ultrasound diagnosis of a mature corpus luteaum in one ovary. Group 3: five buffaloes injected blindly with two doses of 25 mg PGF2α 11-days interval. Group 4: five buffaloes treated with ovsynch protocol. The pattern of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
2
1
0
Order By: Relevance
“…Although the conception rate in the present study was much lower, as reported in river-type buffaloes ( 12 ), it might be linked to breeding differences, management, and the environmental conditions of study sites. Follicular development was rapid, because of development in GPG protocol that corroborates earlier studies ( 17 , 18 ). The increased follicular development in this study was linked to the selection of animals with similar follicular stages at the first injection of GnRH in GPG protocol.…”
Section: Discussionsupporting
confidence: 82%
“…Although the conception rate in the present study was much lower, as reported in river-type buffaloes ( 12 ), it might be linked to breeding differences, management, and the environmental conditions of study sites. Follicular development was rapid, because of development in GPG protocol that corroborates earlier studies ( 17 , 18 ). The increased follicular development in this study was linked to the selection of animals with similar follicular stages at the first injection of GnRH in GPG protocol.…”
Section: Discussionsupporting
confidence: 82%
“…The characteristics of follicular dynamics observed in cyclic Surti buffaloes indicated that 33.33% (n=2) and 66.66% (n=4) of buffaloes had one-and two-waves of follicular development, respectively, while in early pregnant buffaloes one-and two-waves of follicular patterns were in equal proportion (50.00% n=3 each, Table 1, 2). Similar predominant two-wave pattern of follicular development in buffaloes ranging from 53.0 to 83.3% was reported by Baruselli et al (1997), Presicce et al (2005), Noseir et al (2014) and Gaur and Purohit (2019). However, 62.5% of one-wave pattern in water buffaloes (Awasthi et al, 2006) and 53.6% and 83.3% of three wave pattern in Egyptian buffaloes (Barkawi et al, 2009) and in Graded Murrah buffaloes (Satheshkumar et al, 2011) were also reported.…”
Section: Follicular Dynamicssupporting
confidence: 69%
“…It has widened our understanding on the utero‐ovarian functions particularly in cattle. However, limited information on ultrasonographic evaluation of follicular dynamics during the oestrous cycle of buffalo revealed the presence of 1, 2 or 3 wave pattern with two‐wave cycle being common in Murrah (Manik, Singla, Palta, & Madan, ; Taneja, Ali, & Singh, ), Nili‐Ravi (Warriach & Ahmad, ), Egyptian (Barkawi et al, ; Noseir, El‐Bawab, Hassan, & Fadel, ), Mediterranean (Neglia et al, ) and Brazilian (Baruselli et al, ) buffaloes. One‐wave cycle is uncommon in buffalo with the exception of single report on Mehsana breed of buffalo.…”
Section: Introductionmentioning
confidence: 99%